Implementasi Metode Wafa Dalam Meningkatan Kemampuan Baca Al Qur’an Santri Pondok Pesantren Abdi Marier - Muzammil; Fajryan, M. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the implementation of the Wafa Method in improving Quran reading and memorization skills at the Abdi Marier Islamic Boarding School in Paiton, Probolinggo. The background of this research is based on common problems in Quran learning, such as difficulty understanding the makharijul huruf (letter pronunciation), Sifatul huruf (letter pronunciation), and weak memorization consistency due to less interactive learning methods. The Wafa Method, with its visual, audio, kinesthetic, hand gesture, and Hijaz song approaches, is offered as an innovative, enjoyable and systematic solution. The study used a descriptive qualitative approach with a case study design, using observation, interviews, and documentation techniques, involving the boarding school administrators, teachers, and students. Data analysis was conducted thematically with triangulation of sources and methods to ensure data validity. The results indicate that the implementation of the Wafa Method at the Abdi Marier Islamic Boarding School proceeded according to procedure, supported by thorough planning, certified teachers, creative learning media, and high student motivation. As a result, the majority of students were able to read the Quran according to Tajweed rules with an average score above 80, and achieved their memorization target. Challenges encountered included difficulty pronouncing certain verses and the limited effectiveness of the Hijaz song for long verses. This study concludes that the Wafa Method is effective and relevant as an innovation in Quran learning and can serve as a model for other Islamic educational institutions.